Paciente masculino de 74 años con edema agudo del pulmón. - Sánchez Barzola, Karla Paulina (2021)
Acute edema of the lung is the accumulation of fluid in the alveoli that prevents normal oxygenation of the blood and causes hypoxia. It is a medical emergency that must be identified and treated early to avoid further complications or death of the patient. This present clinical case study aims to characterize the respiratory assistance process to a 74-year-old male patient with acute lung edema with a pathological history who enters the emergency area with progressive cough, poor ventilatory mechanics, orthopnea, drowsy level of consciousness, tachypneic and edema of upper and lower extremities. In his are shown, for which he required ventilatory assistance and pharmacological medications to improve his symptoms. The evolution of the patient was satisfactory thanks to the different therapeutic treatments, one of which was non-invasive mechanical ventilation and the pharmacological one. Acute edema of the lung is a complication of either cardiogenic or non-cardiogenic nature that must be treated diagnostic test, specifically his chest X-ray, typical images of acute lung edema as quickly as possible.